Current and future management of Ph/BCR-ABL positive ALL. Issue 6 (June 2014) - Maino, Elena; Sancetta, Rosaria; Viero, Piera; Imbergamo, Silvia; Scattolin, Anna Maria; Vespignani, Michele; Bassan, Renato
Abstract : Following the introduction of targeted therapy with tyrosine kinase inhibitors (TKI) at the beginning of the past decade, the outcome of patients with Philadelphia-chromosome positive acute lymphoblastic leukemia (Ph+ ALL) has dramatically improved. Presently, the use of refined programs with first/second generation TKI's and chemotherapy together with allogeneic stem cell transplantation allow up to 50% of all patients to be cured. Further progress is expected with the new TKI ponatinib, overcoming resistance caused by T315I point mutation, other targeted therapies, autologous transplantation in molecularly negative patients, therapeutic monoclonal antibodies like inotuzumab ozogamicin and blinatumomab, and chimeric antigen receptor-modified T cells. Ph+ ALL could become curable in the near future even without allogeneic stem cell transplantation, minimizing the risk of therapy-related death and improving greatly the quality of patients' life.